Nature-Positive Solutions: Using the ecological benefits framework - Lexicon of Impacts (Lexicon, 2024)
Nature-positive food systems use agricultural practices that regenerate ecosystems while nourishing communities. They balance the needs of people and the planet, ensure long-term food security, reduce environmental harm, and support more resilient rural livelihoods.